Compression Behaviour of Marine Clay in the East Coast of Peninsular Malaysia - Mohamad Sani, Muhammad Afiq (Universiti Teknologi PETRONAS, 2018)
Marine clay is a type of clay that is found in coastal regions around the world and in the northern, de-glaciated regions sometimes it can be quick clay, which always involved in landslides. However marine clay is always problematic due to high deformation and settlement. Therefore, the study of engineering behaviour, strength and compressibility characteristics of marine clay is becoming more important due to certain problems towards the settlement of the structures resting on them such as offshore platforms for oil and gas exploration and reclamation work. This project will discuss a detailed study of compression and strength characteristics of marine clay in the East Coast of Peninsular Malaysia with the objectives of to correlate geotechnical properties of marine clay with depth and also to study the compression behaviour of marine clay. The geotechnical investigation for the marine clay samples include laboratory work for basic soil properties and oedometer test. In the end of this project, the geotechnical properties and compression of marine clay were recorded and the correlations of engineering properties of marine clay and the depth of the marine clay samples were established.